Elasticity of Islamic Law in Social Dynamics (Analysis of E-Comerce A Fiqh Perspective) - Permatasari, Annisa (Faculty of Sharia, IAIN Metro, 2022)
The increasingly advanced development of the world accompanied by the era of globalization and the rapid development of science and technology in several areas of people's lives, such as medical, legal, social and economic, has had a major influence, including legal issues. This research was prepared using the library study method, namely by collecting various reading sources that are in accordance with the outline of the theme, then compiling them into a discussion regarding the law of online buying and selling. To ensure that Islamic law remains dynamic, responsive and highly adaptable to the demands of change, this is by reviving and reviving the spirit of ijtihad among Muslims. In this position, ijtihad is the inner dynamic for the birth of change to guard the ideals of universality of Islam as a shalihun li kulli masa wal makan teaching system.